2017
DOI: 10.1128/aac.01475-16
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Emtricitabine-Loaded Long-Acting Nanoformulation for Prevention or Treatment of HIV Infection

Abstract: Among various FDA-approved combination antiretroviral drugs (cARVs), emtricitabine (FTC) has been a very effective nucleoside reverse transcriptase inhibitor. Thus far, FTC is the only deoxycytidine nucleoside analog. However, a major drawback of FTC is its large volume distribution (averaging 1.4 liters/kg) and short plasma half-life (8 to 10 h), necessitating a high daily dosage. Thus, we propose an innovative fabrication method of loading FTC in poly(lactic-co-glycolic acid) polymeric nanoparticles (FTC-NPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 34 publications
1
50
1
Order By: Relevance
“…The potential of PEG-400 has been studied extensively in solubility enhancement of various drugs [9][10][11][12][13][14][15][16][17][18]. Several formulation approaches including "3D printed controlled release tablets [4], film coated tablets [19], rapidly disintegrating vaginal tablets [20], immediate release tablets [21], vaginal gels [22], liposomal gels [23], microparticulate drug delivery system [24], nanosuspensions [25,26] and polymeric nanoparticles [5,27,28]" were reported to improve antiviral therapy and pharmacokinetic profile of ECT. The equilibrium solubility of ECT in water was found as 112 mg mL −1 at "T = 298.2 K" [1].…”
Section: Introductionmentioning
confidence: 99%
“…The potential of PEG-400 has been studied extensively in solubility enhancement of various drugs [9][10][11][12][13][14][15][16][17][18]. Several formulation approaches including "3D printed controlled release tablets [4], film coated tablets [19], rapidly disintegrating vaginal tablets [20], immediate release tablets [21], vaginal gels [22], liposomal gels [23], microparticulate drug delivery system [24], nanosuspensions [25,26] and polymeric nanoparticles [5,27,28]" were reported to improve antiviral therapy and pharmacokinetic profile of ECT. The equilibrium solubility of ECT in water was found as 112 mg mL −1 at "T = 298.2 K" [1].…”
Section: Introductionmentioning
confidence: 99%
“…The comparative in vitro cytotoxicity of D+T NP vs. D+T solution was evaluated on the TZM-bl cell line using CellTiter-Glo ® luminescent assay method, as described previously (64). Briefly, the TZM-bl cells (10 4 cells/well) in complete HiDMEM medium and PBMCs (10 5 cells/well) in complete RPMI (Thermo Scientific; OK, USA) supplemented with 10% FBS, 1 × AA and 50 U/ml IL-2 (Sigma-Aldrich; MO, USA), were treated in triplicate respectively with D+T NP or D+T solution, at different concentrations (20, 10, 1, 0.1, 0.01 μg/mL each drug concentration) for 96 h. Similarly, the 5% DMSO treated cells and 1×PBS (treatment equal volume) treated cells were the positive and negative control, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The comparative in vitro prophylaxis (PrEP), i.e., protection study between D+T NP vs. D+T solution against HIV-1 NL4-3 , was performed on TZM-bl cells (an HIV-1 infection reporter cell line), and peripheral blood mononuclear cells (PBMCs) was evaluated by following standardized method (9, 64). Briefly, TZM-bl cells (10 4 cells/well) and PBMCs (10 5 cells/well) were seeded in 96-well plate and were treated with different concentrations of D+T (20, 10, 1, 0.1, 0.01 μg/mL each drug concentration) either as D+T NP or as D+T solution.…”
Section: Methodsmentioning
confidence: 99%
“…The compound displayed an improved pharmacokinetic profile over pristine drugs in rats after intravenous dosing without loss of anti-HIV efficacy in vitro [96]. Mandal et al pursued a similar strategy with nanoparticles of PLGA encapsulating elvitegravir (EVG), emtricitabine (FTC) and tenofovir alafenamide (TAF), and found that this combination had HIV prevention effects in humanized mice [97][98][99].…”
Section: Long-acting Antiviral Prodrugsmentioning
confidence: 99%